Numeracy, verbal skills, learning motivation, and self-regulation as predictors of academic success in high school - Warnaningtyas, Murtiatmi; Sulisworo, Dwi; Toifur, Moh (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study explores the influence of numerical literacy, verbal ability, learning motivation in science, and self-regulation on academic achievement among high school students. In today's dynamic educational landscape, success requires more than academic knowledge—it also demands motivation and self-directed learning strategies. This research aimed to examine how these four factors interrelate to predict learning outcomes. Employing an ex-post facto quantitative design, data were collected from 119 high school students across four schools using validated questionnaires and learning outcome assessments. The variables included numerical literacy, verbal ability, and science learning motivation as independent variables, self-regulation as a mediating variable, and academic achievement as the dependent variable. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that all three independent variables significantly and positively affected self-regulation: numerical literacy (β = 0.410, p < 0.001), verbal ability (β = 0.291, p < 0.01), and science learning motivation (β = 0.215, p < 0.05). Furthermore, self-regulation positively influenced academic achievement (β = 0.405, p < 0.001). These findings underscore the critical role of self-regulation as a bridge between cognitive skills and academic performance. By strengthening students’ ability to manage their own learning, educators can enhance academic success, especially in numeracy and science-based learning environments.